Bipolar disorder in the elderly: a cohort study comparing older and younger patients. (5th April 2014) - Nivoli, A. M. A.; Murru, A.; Pacchiarotti, I.; Valenti, M.; Rosa, A. R.; Hidalgo, D.; Virdis, V.; Strejilevich, S.; Vieta, E.; Colom, F.
<x xml:space="preserve">Abstract</x> Objective The purpose of this study was to analyze differences in clinical and socio‐demographic characteristics between older and younger bipolar outpatients paying special attention to depressive symptoms in a large, naturalistic cohort. Method Five hundred and ninety‐three DSM‐IV‐TR bipolar outpatients were enrolled. Clinical characteristics were assessed according to DSM‐IV‐TR (SCID‐I). Subjects were categorized into two groups according to current age (older OBD: age > 65 years; younger‐YBD: age < 65 years). Results About 80% of patients were younger (N = 470), and a fifth were older (N = 123), with a mean age of 77.30 years in OBD. Older patients were more likely to be married, not qualified, bipolar II, with depressive polarity of first episode, higher age at illness onset, higher age at first hospitalization. They were more likely to present with depressive predominant polarity, with lifetime history of catatonic, psychotic and melancholic features, age at illness onset >40 years, as well as suffering from more medical comorbidities when compared to younger bipolars. Conclusion The clinical presentation of bipolar disorder in late life would be defined more frequently by melancholic depressive features and a predominantly depressive polarity. These results suggest that treatment strategies for elderly bipolar patients should focus in the prevention of depressive episodes.